AKTIVITAS ANTIOKSIDAN DAN KADAR TOTAL FENOL DARI EKSTRAK JAMU BERAS KENCUR DENGAN PENAMBAHAN RIMPANG KUNYIT - Fitriansyah, Sani Nurlaela; Riasari, Hesti; Melati, Novi; Simanjuntak, Nela (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Jamu is a traditional medicine from Indonesia. Jamu beras kencur is one of the most popular jamu in Indonesia. Jamu beras kencur are often added with other ingredients to increase the efficacy. Turmeric (Curcuma domestica) was a traditional medicinal plant that has high antioxidant and anti-inflammatory effects. Phenolic compound is the largest secondary metabolite in turmeric. The aimsf this research were to determine antioxidant activity and total phenolic content of extract jamu beras kencur wich was added of various concentrations of turmeric and the differences boiling time in processing jamu preparations. The processing of jamu beras kencur with the addition of turmeric with boiling time (15 minutes and 30 minutes). Variation of concentration of tumeric were 5%, 10% and 20%. The concentration of turmeric used addition 5%, 10% and 20. Each preparation was extracted using ethyl acetat. Aantioxidant activity of each extract was performed by DPPH method wich demonstrated as IC50 DPPH. Determination of total phenolic was performed by UV-Vis spectrophotometry and expressed in g GAE/100 g extract. The highest antioxidant activity (IC50 of 485 μg/mL) and the highest total phenolic (41.336 g GAE /100 g extract) was given by jamu beras kencur wich 20% turmeric and 15 min boiling time. Addition of turmeric and differences of boiling time in processing jamu preparations can affect antioxidant activity and total phenolic content.